The Iban Visual Culture: Miring - Yow, Chong Lee; Noria, Tugang; Anna, Durin (UNIMAS Publisher, 2017)
Iban Community is one of the biggest community groups that live in all parts of Sarawak. In addition, the Iban community in contemporary erahas embraced major religions such as Christianity and Islam.